Designing POGIL Based Student Worksheets for Buffer Solution Learning at SMAN 2 Sawahlunto - Wanti, Sri; Mawarnis, Elvy Rahmi; Herman, Mimi (Universitas Pendidikan Mandalika, 2024)
The purpose of this study was to produce a valid and practical Process Oriented Guided Inquiry Learning (POGIL)-based Student Worksheet (LKPD) on 11th Grade Class Buffer Solution Material at State Senior High School (SMAN) 2 Sawahlunto. This research uses the Research and Development research method with the 4-D development model (define, design, develop, and disseminate). However, the stages in research with this 4-D model are only carried out from the first to the third stage, namely the define stage aims to get an overview of field conditions, the design stage aims to compile and design POGIL-based Student Worksheets (LKPD) on buffer solution material, and the develop stage aims to continue the POGIL-based LKPD on buffer solution material that has been designed with validity and practicality tests. The research instruments used were validation sheets and response questionnaire sheets. The validation sheet was filled by 2 lecturers and 1 chemistry educator. The response questionnaire sheet was filled by 25 of 11th grade students and 2 chemistry educators of SMAN 2 Sawahlunto. The results showed that 1) POGIL-based LKPD on buffer solution material meets the valid criteria with 85.42% validation results. 2) POGIL-based LKPD on buffer solution material has met the practical criteria with educator practicality response questionnaire results of 92.31% and student response questionnaire results of 82.15%.